Digitising (Romanian) Cyrillic using Transkribus: new perspectives. - Burlacu, Constanța; Rabus, Achim (Diacronia, 2021)
In this paper we discuss the application of the software platform Transkribus (transkribus.eu), an AI-assisted tool for Handwritten Text Recognition (HTR), to 16th century Romanian manuscript and printed sources using Cyrillic scripts. After an overview of the basic functionality of the HTR technology and Transkribus, we discuss the Romanian and bilingual Slavonic-Romanian sources we used, give an insight on training specific and generic as well as smart (i.e. transliterating from Cyrillic into Latin script) models, evaluate their performance and discuss implications of HTR for philological research in the Digital Age. We conclude with an outlook on future research perspectives.